2020
DOI: 10.33271/nvngu/2020-4/053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical and thermal treatments on microstructural transformations in cast irons and properties of synthesized diamond crystals

Abstract: Influence of MechAnIcAl AnD therMAl treAtMents on MIcrostructurAl trAnsforMAtIons In cAst IronsAnD propertIes of synthesIZeD DIAMonD crystAls purpose. To analyze how the structural transformations in the cast iron metal matrix near graphite inclusions influence the features of synthesis of metastable diamond crystal on diamond polycrystals (substrate) synthesized by shockwaves.Methodology. In experiments, we used the laserinduced detonation of explosive charges to create a flat shockwave front and employed che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…2. Scheme of initiating a light-sensitive explosive composite by laser radiation: laser beam (1), diaphragm (2), laser beam after diaphragm (3), diverging lens (4), scattered laser beam (5), LSEC layer (6), explosive charge or the processed material (7). V. N. Viliunov, 1984, and others.…”
Section: Experimental and Theoretical Studiesmentioning
confidence: 99%
“…2. Scheme of initiating a light-sensitive explosive composite by laser radiation: laser beam (1), diaphragm (2), laser beam after diaphragm (3), diverging lens (4), scattered laser beam (5), LSEC layer (6), explosive charge or the processed material (7). V. N. Viliunov, 1984, and others.…”
Section: Experimental and Theoretical Studiesmentioning
confidence: 99%
“…The authors of [61,84,85] suggested that relic diamond particles could be found in other bodies of the Solar Sys tem, e. g. meteorites [86]. This idea was later (1987) proved in the research [1].…”
Section: A Ke Rs T E Rtmentioning
confidence: 99%
“…Exposure to a shock wave occurs with simultaneous heat ing of carboncontaining alloys [59], additional thermalme chanical [60] and thermal cycling treatment of alloys [61] ei ther before or after shockwave treatment. In addition to the above methods, electromagnetic treatment of a solid carbon containing medium after synthesis in highpressure chambers was used [63,64].…”
mentioning
confidence: 99%
“…The method for forming a plane detonation wave is reliable. Evidence is a number of positive experimental results obtained during the formation of plane shock waves in the material under study directly by a plane detonation wave front at an angle of 0° relative to the surface of the material facing the striker [33,34], or by a detonation wave front sliding at an angle of 90° to the generatrix of the cylinder surface [35], or by the impact of a fl at plate accelerated by the products of the PEC explosion [36], including in problems of studying the nature of the fl ow of matter behind the front of the bow shock [37].…”
mentioning
confidence: 99%